Melatonin ameliorates renal fibroblast‐myofibroblast transdifferentiation and renal fibrosis through miR‐21‐5p regulation. Issue 10 (3rd April 2020) - Li, Ningning; Wang, Zhan; Gao, Fenglan; Lei, Yanfei; Li, Zhenzhen
Abstract: Fibroblast‐myofibroblast transdifferentiation (FMT) is widely recognized as the major pathological feature of renal fibrosis. Although melatonin has exerted antifibrogenic activity in many diseases, its role in renal FMT remains unclear. In the present study, the aim was to explore the effect of melatonin on renal FMT and the underlying mechanisms. We established the transforming growth factor (TGF)‐β1 stimulated rat renal fibroblast cells (NRK‐49F) model in vitro and unilateral ureteral obstruction (UUO) mice model in vivo. We assessed levels of α‐smooth muscle actin (α‐SMA), col1a1 and fibronectin, STAT3 and AP‐1, as well as miR‐21‐5p and its target genes (Spry1, PTEN, Smurf2 and PDCD4). We found that melatonin reduced the expression of α‐SMA, col1a1 and fibronectin, as well as the formation of α‐SMA filament in TGF‐β1‐treated NRK‐49F cells. Meanwhile, melatonin inhibited STAT3 phosphorylation, down‐regulated miR‐21‐5p expression, and up‐regulated Spry1 and PTEN expression. Moreover, miR‐21‐5p mimics partially antagonized the anti‐fibrotic effect of melatonin. For animal experiments, the results revealed that melatonin remarkably ameliorated UUO‐induced renal fibrosis, attenuated the expression of miR‐21‐5p and pro‐fibrotic proteins and elevated Spry1 and PTEN expression. Nevertheless, agomir of miR‐21‐5p blocked the renoprotective effect of melatonin in UUO mice. These results indicated that melatonin could alleviate TGF‐β1‐induced renal FMT and UUO‐induced renal fibrosis through down‐regulation of miR‐21‐5p. Regulation of miR‐21‐5p/PTEN and/or miR‐21‐5p/Spry1 signal might be involved in the anti‐fibrotic effect of melatonin in the kidneys of UUO mice.